The - Dumas, Alexandre (Oxford University Press, 2003)
It is the year 1627, and young D'Artagnan comes to Paris with a dream - to become a King's Musketeer. Three of these brave soldiers - Porthos, Athos and Aramis - soon become his friends. After a short time d'Artagnan has fallen in love - and into great danger. Can the three musketeers and d'Artagnan fight against the evil plans of the beautiful Milady and the cruel Cardinal Richelieu?